Incidence of antibodies reactive with toxic shock syndrome toxin 1 in bovine milk. - Thompson, N E (1986)
Fourteen samples of bovine milk, purchased in six states, were found to contain significant antibody titers to toxic shock syndrome toxin 1. This reactivity seems to have been due primarily to antibodies of the immunoglobulin A class. Some of these antibodies survived the cheese-making process.